Using Artificial Intelligence in Teaching the Interaction of Endocrine Gland Hormones – A New Stage of Digital Education (KIUT Publication, 2025)
The endocrine system plays a crucial role in regulating the body’s vital processes — growth, metabolism, reproductive activity, and homeostasis. The hormones of the endocrine glands form a complex and closely interconnected system. This topic is challenging for biology and medical education, and traditional methods often cause difficulties for many students. Modern digital technologies, especially artificial intelligence (AI), serve as an important tool in simplifying this complexity. With the help of AI, studying the endocrine system becomes interactive, visual, and personalized, which helps students gain a deeper understanding of the topic.